Contrasting diversity of testate amoebae communities in Sphagnum and brown-moss dominated patches in relation to shell counts - Lizoňová, Zuzana; Horsák, Michal (European journal of protistology, 2017)
Ecological studies of peatland testate amoebae are generally based on totals of 150 individuals per sample. However, the suitability of this standard has never been assessed for alkaline habitats such as spring fens. We explored the differences in testate amoeba diversity between Sphagnum and brown-moss microhabitats at a mire site with a highly diversified moss layer which reflects the small-scale heterogeneity in groundwater chemistry. Relationships between sampling efficiency and sample completeness were explored using individual-based species accumulation curves and the effort required to gain an extra species was assessed. Testate amoeba diversity differed substantially between microhabitats, with brown mosses hosting on average twice as many species and requiring greater shell totals to reach comparable sample analysis efficiency as for Sphagnum. Thus, for samples from alkaline conditions an increase in shell totals would be required and even an overall doubling up to 300 individuals might be considered for reliable community description. Our small-scale data are likely not robust enough to provide an ultimate solution for the optimization of shell totals. However, the results proved that testate amoebae communities from acidic and alkaline environments differ sharply in both species richness and composition and they might call for different methodological approaches.
Keywords: ekologie; Bryophyta; ekosystém; rašeliníky; Sphagnopsida; Ecosystem; Testate amoebae; biodiverzita; Ecology; Amoeba; Methodology optimization; Sphagnum; Spring fens; Brown mosses; Individual counts; Biodiversity